ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN PERTUMBUHAN PENDUDUK TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KABUPATEN/KOTA PROVINSI SUMATERA SELATAN - Trisia Oktarima; Nazipawati Nazipawati (Ekonomika, 2021)
This research aims to analysis the effect of economic growth and population growth on the open unemployment rate in districts/cities of South Sumatera Province in period 2010-2019. The type of data used in this research is secondary data in the form of panel data. The Methode of data analysis used are panel data regresson. The results of analysis indicates that simultaneously economic growth and population growth have positive and significant effect on the open unemployment rate in districts/cities of South Sumatera Province in period 2010-2019. Partially show that economic growth has a positive and significant effect on the open unemployment rate, while population growth has a positive and no significant effect on the open unemployment rate in districts/cities of South Sumatera Province in period 2010-2019. The value of determination coefficient show that 0.036337. its show that open unemployment rate variation can be explained by economic growth and population growth of 3,6337% whereas 96,3663% as residual explained by other variable outside the model in this research.